Neuromyelitis optica in a paediatric patient: a case report - Ranabijuli, Pradeep Kumar; Pankaj Sitaram, Arangale; L. A., Nazparveen; Kumari, Sita (International Journal of Contemporary Pediatrics, 2024)
Neuromyelitis optica is a multifocal demyelinating disease of the central nervous system that predominantly affects the spinal cord and optic nerves, with variable clinical features including motor weakness in limbs, bowel and bladder affection and loss of vision. The disease is characterized by poor or no recovery. Magnetic resonance imaging (MRI) of spine with contrast shows hyperintense lesions involving contiguous segments with a normal MRI brain. CSF studies shows anti aquaporin 4 antibodies. Visual evoked potential of eyes shows marked reduction of optic nerve function. We report a case of eight year old girl who presented with diminished vision in eyes (right >left) and weakness in all four limbs. Clinical features and investigations were suggestive of NMO. She was treated with inj. methylprednisolone for 5 days followed by oral prednisolone in tapering dose for 6 weeks. The child improved of hemiparetic gait and power in the left side. Vision in the left eye did not deteriorate further. Repeat MRI showed the resolution of previous spinal lesions. Follow up of the child over seven years has multiple admissions due to relapses. In the third admission child was given again 5 days of inj. methylprednisolone followed by azathioprine for two months. On the seventh admission due to relapse, inj. rituximab 500 mg and inj. methylprednisolone 500 mg was given and repeated every 6 months. In the last follow up in June 2024, the child is clinically stable with improvement in gait and no further deterioration of vision and no bowel or bladder affection.